Influence of visceral pregestational obesity on plancental and fetal development - Catherina Capote Guitián; Gipsis Suárez Román; Nínive Sebasti Núñez López; Gregorio Belo; Manuel Fransisco Da Costa; Teresa C. Valdés Bacallao; Yoneidis Borges Guilarte; Sonia Clapés Hernández; Sebastián Andrés San Martín Henrique (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: Pregestational obesity, especially visceral obesity, is associated with the development of complications for the fetus, the mother and the neonate. The analysis of the placenta is a key to understanding the development of these complications. Objective: To evaluate the influence of visceral pre-gestational obesity on the placental and fetal development in rats. Material and Methods: Female Wistar rats received subcutaneous injections of monosodium glutamate (4 mg/ g of body weight) during the neonatal period to induce obesity or NaCl 0.9 % (Controls). At 90 days of age, obesity was confirmed and at 120 days of life they were mated overnight with healthy males of the same substrain. Gestational day 0 was defined when sperms were found in vaginal smear. The day 20 of gestation, euthanasia was practiced for obtaining of placentas and fetuses. Placental biochemical, and structural variables and indicators of growth and fetal development were determined. Results: In the placentas of obese rats, reserve cells of glycogen, triglycerides content and the area of the trophoblast were increased. The area of maternal blood was decreased. The obese group also showed an increased placental index. Fetuses of obese mothers had smaller tail length, cranial diameters and ossification sites numbers. Conclusions: Pregestational obesity exerted a harmful effect on placental development, provoking fetal growth restriction.  This may be due to a decrease in the maternal-fetal interchange of nutrients and oxygen because of ectopic accumulation of lipids in the labyrinthine zone.